Polypharmacy among adults aged over 65 years - Patrycja Misztal-Okońska; Magdalena Młynarska; Mariusz Goniewicz; Dominika Ceglińska (Kazimierz Wielki University, 2017)
The term polypharmacy is defined as using many drugs without knowing the mechanism of their effects on the body, interactions between them, or taking at least one drug for which there are no indications.The phenomenon of polypharmacy occurs especially in the elderly and is most often the result of treatment of one patient's several conditions by different doctors. Polypharmacy is associated with increased risk for drug interactions, adverse drug reactions, and hospitalization of the elderly. . Polypharmacy is increased also by the use of over-the-counter (OTC) medicines, dietary supplements or herbs without consulting a doctor.   The purpose of the research was to study behaviors related to medication and diet supplementation by people aged over 65 years.             Study group and method. The research was conducted in a senior club in Wąwolnica (40 people) and in the spa sanatorium in Nałęczów (60 people). A total of 100 people over 65 years were examined. The research method was a diagnostic survey, and the research tool was the author's survey questionnaire.             Results. The majority (67%) of respondents were between 65 and 69 years old, followed by 23% of 70-79 year olds. The average amount of drug intake per person is 4 drugs per day. Over half of respondents (60%) use self-treatment. 20% of respondents admit to take more than 1 antibiotic at the same time, while only 28.6% of the subjects have knowledge of how to take the probiotic during antibiotic therapy properly. As many as 10% of the respondents declared that they were hospitalized due to polypharmacy.             Conclusions. The results of the study show that people aged over 65 years may be at risk of polypharmacy, that is why physicians (GP's in particular) should remember to remind the elderly of the need to consult every drug they take with every doctor they consult with. Particular attention should be paid to the education of patients regarding the proper way of taking probiotic during antibiotic therapy.